Analysis of the relationship between systematic and unsystematic risks for a sample of companies and banks listed on the Iraq Stock Exchange for the period (2016-2024) - Alaa Mohsin Muttlaq Al-Daamy; Ali Faisal Kazim Al-Daamy; Safaa Yassin Shake (Technium Social Sciences Journal, 2025)
Therefore, this study aimed to analyze the relationship between systemic risk and nonsystemic risk for a sample of selected companies and banks listed on the Iraq Stock Exchange for the period 2016 to 2023. The systemic risk was measured through Beta The research sample included four banks and one industrial company for a period of ten years (Mosul Bank, Baghdad Soft Drinks, United Bank, Baghdad Bank, Middle East Bank), as the financial statements of the banks were obtained through the annual reports published in the Iraq Stock Exchange. Simple panel data regression was used through the statistical program (EViews v.12) according to the models (regression, variance, beta), and the research reached a set of results, the most important of which is the existence of a statistically significant effect of systemic and non-systemic market risks on the continuity of banks. In light of this, the research came up with a number of recommendations, the most important of which are that commercial banks should pay more attention to measuring systemic risks and the importance of diversification in foreign investment to get rid of systemic risks, and also pay attention to measuring non-systemic risks through the Value at Risk (VaR) method to identify and address weaknesses and deficiencies, as well as identify and increase strengths